The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/v13010068
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Derived Organotypic Epithelial Rafts Model Phenotypes in Juvenile-Onset Recurrent Respiratory Papillomatosis

Abstract: Juvenile-onset recurrent respiratory papillomatosis (JoRRP) is driven by human papillomavirus (HPV) low-risk strains and is associated with significant morbidity. While previous studies of 2D cultures have shed light on disease pathogenesis and demonstrated the utility of personalized medicine approaches, monolayer cultures lack the 3D tissue architecture and physiology of stratified, sequentially differentiated mucosal epithelium important in RRP disease pathogenesis. Herein we describe the establishment of J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 28 publications
(37 reference statements)
1
21
0
Order By: Relevance
“…Proliferation index increased to a median of 3.4% in diseased murine laryngeal tissues, and Ki67-expressing cells were found above the basal layer of the epithelium. A similar expansion of proliferating cells has been observed in RRP lesions [ 23 ] and in MmuPV1-induced lesions of the oral cavity and the anogenital tract [ 74 , 75 , 76 , 77 ]. Like the larynx, we found that proliferation and hyperplasia increased in trachea with MmuPV1-induced disease.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Proliferation index increased to a median of 3.4% in diseased murine laryngeal tissues, and Ki67-expressing cells were found above the basal layer of the epithelium. A similar expansion of proliferating cells has been observed in RRP lesions [ 23 ] and in MmuPV1-induced lesions of the oral cavity and the anogenital tract [ 74 , 75 , 76 , 77 ]. Like the larynx, we found that proliferation and hyperplasia increased in trachea with MmuPV1-induced disease.…”
Section: Discussionsupporting
confidence: 72%
“…Healthy vocal fold epithelium is characterized by proliferating cells in the basal and parabasal layers and differentiated suprabasal cells [ 20 , 21 , 22 ]. Human RRP lesions are characterized by an expanded basal compartment, proliferating cells throughout epithelial layers, and decreased differentiation [ 23 , 24 , 25 , 26 , 27 ]. High-risk HPVs are known to suppress apoptosis in infected cells [ 28 ], and apoptosis may play a role in vocal fold epithelial diseases [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Models of low-risk HPV-associated diseases, including RRP, are limited [ 41 ]. Current preclinical models of RRP are limited to in vitro organotypic raft culture and xenografts, which are typically used at early passages to study short-term viral and host gene expression [ 42 , 43 , 44 , 45 ]. In the sole reported experimental infection of an animal larynx with an animal papillomavirus, canine oral papillomavirus (COPV) was injected into the supraglottic laryngeal tissues of canines [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biopsies were obtained and used to establish primary mucosal squamous epithelial cell cultures as previously described [ 36 ]. Importantly, matched biopsy sets of papilloma and non-diseased tissue were obtained per patient.…”
Section: Methodsmentioning
confidence: 99%
“…2D cell pellets were collected from early passage (passage 2–4) primary cells derived from papilloma biopsies, extracted for RNA, and run by RT-qPCR using HPV-strain specific primers to determine HPV6 versus HPV11 genotype as previously described [ 36 ].…”
Section: Methodsmentioning
confidence: 99%